Analysis of Support of the Knowledge of High School Mathematics to Mathematical Calculation Literacy - Han, Qi; Yang, Zezhong (American Journal of Creative Education, 2020)
According to the division of three levels and four aspects of mathematical calculation literacy in Chinese General Senior High School Mathematics Curriculum Standard (2017 Edition), by using the way of questionnaire and statistical analysis, we analyze the degree of support of the knowledge (including knowledge presentation and proposition derivation) in the first volume of compulsory textbook of general high school mathematics to mathematical calculation literacy. The results show that the knowledge presentation part of the textbook supports the implementations of ten aspects of mathematical calculation literacy. In all these ten aspects, the support to level 1 of knowledge and skill is the best. However, level 3 of knowledge and skill, and level 3 of thinking and expression are not supported. As for the proposition derivation part of the textbook, it supports the implementations of 11 aspects of mathematical calculation literacy. Among them, level 1 of situation and problem is supported mostly, while level 3 of thinking and expression is not. Therefore, in order to use knowledge more effectively, we suggest that the knowledge in the textbook should be selected and elaborated. Only in this way, can we use them to the maximum extent and help more to cultivate students’ mathematical calculation literacy.